Effect of DC Biased Voltage and Ion Temperature on Bounded Ion-Ion Plasma - Maskey, Anish; Deuja, Atit; Basnet, Suresh; Khanal, Raju (Journal of Institute of Science and Technology, 2020)
A one dimensional particle-in-cell (PIC) simulation method has been employed to study the effect of DC voltage and ion temperature on the properties of ion-ion plasma bounded by two symmetrical but oppositely biased electrodes. It is assumed that the ion-ion plasma is collisionless and both the positive and negative ion species have the same mass, temperature, and degree of ionization. Simulation results show that the formation of sheath and presheath regions and fluctuation of plasma parameters in that region are affected by the biasing voltage and ion temperature. It was found that the magnitude of the electrostatic electric field at the vicinity of biasing electrodes was affected by the biasing voltage and ion temperature as well. This strong electric field close to the electrodes further prevents the flow of charged particles towards the electrodes. The presence of a non-zero electric field at the quasineutral region suggests a presheath region similar to the electron-ion plasma. In the quasineutral region, the density of ions increased with the increase in biasing voltage and decreased with the increase in temperature of isothermal ions. Furthermore, the phase space diagrams for the ions were obtained which indicated different regions of the plasma. The positive ions acquire negative velocity towards the negatively biased electrode and the negative ions acquire positive velocity towards the positively biased electrode.